STUDI TENTANG MONUMEN PAHLAWAN TIDAK DIKENAL DI TAMAN MELATI MUSEUM ADITYAWARMAN PADANG - BIMA PRATAMA, Dra. Lisa Widiarti, M.Sn., Dr. Ramalis Hakim, M.Pd. (Universitas Negeri Padang, 2018)
Monument of the unknown hero is a work of Monumental. Was used as a land mark in Kenagarian District of Padang Barat Padang, which serves as a symbol of the struggle of the people of Padang city. Lack of public appreciation of the monument, so the condition of unknown hero monument less attention and began to disappear from the view of the people who visit Taman Melati, people who visit in Taman Melati Padang many who do not know the history or just merely berselfy ria and do not know what the name of the monument .This research uses qualitative methodology with descriptive research type, that is describe everything found in field according to reality. Descriptive method aims to describe or analyze a research result but not used to make wider conclusions. The results show that the construction of unknown hero monument is inseparable from the history contained in the monument, namely the history of unknown hero's struggle against the belasting policy and the occurrence of war against Dutch aggression in 1950 in the city of Padang. The shape of the monument takes place from the foundation, the base of the figure, and there is a male figure depicting a warrior fighter against the Dutch.Kata kunci: Bentuk, Fungsi, Makna